47.4k views
0 votes
Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!

Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz-example-1
User Pubudu
by
5.2k points

2 Answers

3 votes

Answer:

4

Explanation:

4 Is the Answer because you have to multiply 4 to all the N's. Which means you have to multiply 4 by 3 which equals 12. Then 2+4=6. Then you would do 12-6=6. There's your answer. Here is the equation if it were like the problem: 12 - (2+4). I'm sure you can figure out the rest. Thanks. If you find any fault in my answer let me know! Have a good day!

User Phils
by
5.4k points
5 votes

Answer: n=4

Explanation:

Given

3n-(2+n)=6

Expand Parenthesis (REMEMBER TO CHANGE SIGNS)

3n-2-n=6

Combine like terms

2n-2=6

Add 2 on both sides

2n-2+2=6+2

2n=8

Divide both sides by 2

2n/2=8/2

n=4

Hope this helps!! :)

Please let me know if you have any questions

User Ilya Karpeev
by
6.0k points